2004
DOI: 10.1074/jbc.m406743200
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of p53 Functions by Daxx and the Involvement of MDM2

Abstract: In normal cells p53 activity is tightly controlled and MDM2 is a known negative regulator. Here we show that via its acidic domain, Daxx binds to the COOH-terminal domain of p53, whose positive charges are critical for this interaction, as Lys to Arg mutations preserved, but Lys to Ala or Ser to Glu mutations abolished Daxx-p53 interaction. These results thus implicate acetylation and phosphorylation of p53 in regulating its binding to Daxx. Interestingly, whereas Daxx did not bind to p53 in cells as assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 51 publications
9
62
0
Order By: Relevance
“…We then wished to assess whether p53-activating chemotherapeutical agents could relieve E1B-mediated repression. In keeping with published reports (26,35) 8). A similar pattern of p21 expression was also observed in cells treated with both TSA and 5-FU (lanes 10 -12 in Fig.…”
Section: E1b Represses P21 Expression In Glioblastoma Ln-229supporting
confidence: 77%
See 1 more Smart Citation
“…We then wished to assess whether p53-activating chemotherapeutical agents could relieve E1B-mediated repression. In keeping with published reports (26,35) 8). A similar pattern of p21 expression was also observed in cells treated with both TSA and 5-FU (lanes 10 -12 in Fig.…”
Section: E1b Represses P21 Expression In Glioblastoma Ln-229supporting
confidence: 77%
“…The cells were then processed for dual-luciferase assays (Promega) 48 h after transfection. Firefly luciferase activity was normalized against sea pansy luciferase activity as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Daxx-␤ and Daxx-␥ lacking this domain displayed a strongly diminished interaction with p53. However, analogous to the reduced interaction with PML, the binding of Daxx-␤/-␥ to p53 was not totally absent which confirms prior observations that N-terminal parts of Daxx could be also implicated in p53 binding (19,20). This interaction (Daxx/p53) is accompanied with a recruitment of p53 to PODs, thereby corroborating recent reports that p53 co-localizes with PML in PODs and that Daxx display a co-localization pattern with p53 in subnuclear dot-like structures (19,28,29).…”
Section: Discussionsupporting
confidence: 75%
“…7B). This is consistent with recent observations that N-terminal parts of Daxx could also be implicated in binding to p53 (19,20). After co-expression of Daxx with empty GFP vector, which served as negative control, even with longer exposure no Daxx protein could be detected in the corresponding precipitate.…”
Section: Neither Daxx Nor Daxx-␤ or Daxx-␥ Is An Enhancer Of Cd95-medsupporting
confidence: 79%
“…More recently, it was found that Daxx can modulate the function of mdm2 regulating therefore DNA damage-induced p53 activation. 12,13 The importance of Fas and FasL in lymphocyte homeostasis and peripheral tolerance is revealed by the identification of mutations in their genes in both mice and humans where both lymphoproliferation and autoimmunity are observed. 14 Mice deficient in FADD, caspase 8 or FLIP (through either a germline deficiency or an overexpression of a dominant-negative form (DN) form) do not develop such pathological features, but present an unexpected defect in T-cell activation.…”
mentioning
confidence: 99%